Faith-Based approaches to vaccine misconception: a systematic literature review of religious messaging - Wan Mohd Ghazali, Wan Norshira; Muhammad Husni, Ahmad; Mohamed, Shafizan; Yusoh, Mohd Helmi; Abdul Manan, Kamaruzzaman; Mohd Nasir, Nur Shakira (IIUM Press, 2025)
Since more and more individuals rely only on the internet for information, falsehoods on health-related matters are spreading more quickly. When it comes to a religious stance around vaccinations, false information may be more difficult to change since it affects an individual’s faith. To combat religious vaccine misconception, this research explored Scopus, Google Scholar, MyCite, EBSCOhost, and FatwāMujamma’ databases using a systematic literature review (SLR) procedure. 5076 studies on vaccination and religion were identified between 2016 and 2021. After a thorough screening process, only 25 studies reflecting religious discussion on vaccination were extracted for analysis. Designed to synthesise religious sources, this SLR identified Qur’ānic passages and Hadith supporting vaccine uptake. The results were also synthesised according to fatwā across types of vaccination. This paper followed PRISMA in reporting the SLR study. In short, this study is significant as it provides evidence supporting the need for vaccination to safeguard the welfare and prosperity of the Muslim community. It should be noted that religious messages must be incorporated into health communication intervention strategies for educators, religious leaders, and advocates to inform the public about the importance of vaccinations. This review further offers the Malaysian Health Ministry a reference to be included as part of its strategies from Islamic perspectives in combating vaccine refusal and anti-vaccination movement among the Muslim community, as they compose the majority of the population.